Pengaruh Pembelajaran Kooperatif Think Pair Share Terhadap Hasil Belajar Materi Pelajaran Agama Buddha Kelas XI SMA Singosari Delitua Tahun Pelajaran 2019/2020 - Astari, Liely; Lisniasari, Lisniasari; Romidi, Romidi (SEKOLAH TINGGI AGAMA BUDDHA DHARMA WIDYA, 2021)
Education has an important role because education is a means to improve quality human resources (HR). There are many students who only have high academic grades but in fact they don't understand it. The difference from the ability of students to memorize the lesson they have learned different from the ability of students to understand the lesson they have learned. One way that educators can do to improve the quality of education is new learning strategy. Educators are obliged to help students understand the concept of subject matter to improve student learning outcomes like Cooperative Learning Think Pair Share. Cooperatif Learning think pair share provides opportunities for students to discuss learning subject matter together and share the results of discussions of subject matter. This study uses data collection techniques, that is cognitive test, in the form of a written test through pre-test and post-test given to students, psychomotor tests in the form of practice tests and affective tests in the form of a questionnaire. The results obtained indicate that students have work together and cooperative skills in cooperative learning think pair share. The magnitude of the influence of think pair share cooperative learning is 3,69% which has a positive direction of 6,08%, then the researchers draw the conclusion that there is a positive influence from cooperative learning think pair share for learning outcomes subject matter Buddhist Studies class XI SMA Singosari Delitua school year 2019/2020.